FINANCIAL RESOURCES AS A STRATEGIC DRIVER ON PERFORMANCE OF AGENCY BANKING IN COMMERCIAL BANKS IN KENYA - Martin N. Mbugua; Margaret Oloko; Jared Deya (International Journal of Innovative Technologies in Social Science, 2022)
The study sought to establish the influence of financial resources on the performance of agency banking in commercial banks in Kenya. The study reviewed previous studies done to support the research objectives from which the research gaps were extracted. The study used descriptive survey research design. The target population for this study was the 18 commercial banks in Kenya licensed by Central Bank of Kenya to operate agency banking. The branch managers, ICT managers, operations managers, human resource managers and customer relations managers were the key targets respondents in the study. Primary and secondary data was collected using questionnaires and checklist guide respectively. Inferential analysis was carried out to establish the relationship between the independent variables and the dependent variable. The study established that Financial Resources had a positive significant influence on the performance of agency banking among the commercial banks in Kenya. The financial resources availed to agency banking through shareholders’ fund, liquidity ratio and value of assets also positively influenced the performance of agency banking. The study concluded that financial resources were essential in steering the performance of agency banking thus recommending that the commercial banks through the management ought to uphold these strategic drivers in order to enhance the performance of agency banking.